Counseling on Insulin Injection Timing Management for Type II Diabetes Mellitus Patients at Grandmed Hospital Lubuk Pakam - Pitriani, Pitriani; Hayati, Kardina; Sitepu, Abdi Lestari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Type II Diabetes Mellitus (DM) is a chronic condition whose prevalence continues to rise in Indonesia. Although insulin therapy is commonly administered to patients, their knowledgeparticularly regarding the appropriate timing of insulin injection remains relatively low. This limited understanding may contribute to unstable blood glucose levels, highlighting the need for personalized management strategies, especially in the scheduling of insulin administration. This community engagement program was implemented through health education and counseling methods aimed at promoting a more proactive and preventive approach in the management of Type II DM. The educational strategy adopted was both informative and interactive, designed to enhance the comprehension of 18 outpatient participants diagnosed with Type II DM. The findings demonstrated that participants showed strong enthusiasm throughout the intervention, driven by a recognized need to better understand insulin injection timing and postprandial glucose control. Moreover, there was a measurable improvement in knowledge, with an average increase of 27.7 points from pre-test to post-test assessments. This outcome affirms the effectiveness of the health education activity in achieving the intended objectives of the program. Participants also expressed interest in the continuation of similar educational efforts in the future. Additionally, the distribution of educational materials in the form of leaflets containing guidance on insulin injection schedules, meal timing, and adherence to effective insulin therapy protocols served as a practical tool for application at home. In conclusion, this educational initiative successfully enhanced patient health literacy and provided effective guidance to support diabetes self-management. Furthermore, the activity contributed to improving the overall quality of life for patients by supporting better glycemic control and preventing long-term complications.